"This Is Still a Work in Progress" Common Ground, Littleton, New Hampshire - Hall, Mair.; Walker, Pam; Syracuse Univ., NY. Center on Human Policy ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1997)
This site-visit report describes Common Ground, a program located in New Hampshire that supports 52 people with developmental disabilities, including some with severe and multiple impairments, in a broad range of individualized, integrated daytime activities, including supported and competitive employment, self-employment, volunteer work, and the pursuit of recreational/leisure activities. The organization of Common Ground, its development, and the changes it undertook in order to provide individualized support are discussed. Three key areas of innovative practices and challenging dilemmas at Common Ground are reviewed, including agency change, self-determination, and valued community roles and membership. Lessons learned are that: (1) change is not a formula; (2) new agency roles mean relinquishing control; (3) new staff roles mean reliance on the community; (4) support for staff is key to successful change; (5) change involves trade-offs that may bring both advantages and disadvantages; (6) individualized funding is needed to promote self-determination; (7) self-employment opportunities are important; (8) advocacy/self-advocacy must be encouraged; (9) roles and relationships take time; (10) roles and relationships require shared community place and experiences; and (11) Common Ground only supports people for a limited part of their day. (CR)
Sponsoring Agency: National Inst. on Disability and Rehabilitation Research (ED/OSERS), Washington, DC.
Contract Number: H133D50037.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adults; Agency Role; Change Strategies; Community Programs; Mental Retardation; Organizational Change; Recreational Activities; Self Determination; Severe Disabilities; Social Integration; Social Services; Supported Employment; Reports, Descriptive